2014
DOI: 10.1080/10256016.2014.988151
|View full text |Cite
|
Sign up to set email alerts
|

13C discrimination between diet, faeces, milk and milk components

Abstract: Stable isotope analysis is a fundamental tool in food origin and authenticity testing. Its use in livestock production requires knowledge of isotope discrimination between product and diet. Here, we report (13)C discrimination ((13)Δ) for milk, milk components (fat, casein and lactose) and faeces in eight lactating dairy cows, which grazed pasture or were fed fresh pasture herbage in the stall. Cows were supplemented with grain maize at 1.72 kg d(-1) (dry matter). Feed components were collected daily, and faec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Different studies have analyzed the link between feeding and produced milk isotopic signals. [22][23][24][25]36 In the case of this work, analyzing the isotopic carbon and nitrogen ratio values calculated from the mixing model (model 1) (that reflects the feed isotopic signal and the proportion given to the buffaloes), a lower value for 15 N with respect to that measured in milk was found. This result was reported also in Cantalapiedra-Hijar et al, 25 where ruminant animal and milk proteins were found enriched with regards to their diet, due to the metabolic pathways of these animals.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Different studies have analyzed the link between feeding and produced milk isotopic signals. [22][23][24][25]36 In the case of this work, analyzing the isotopic carbon and nitrogen ratio values calculated from the mixing model (model 1) (that reflects the feed isotopic signal and the proportion given to the buffaloes), a lower value for 15 N with respect to that measured in milk was found. This result was reported also in Cantalapiedra-Hijar et al, 25 where ruminant animal and milk proteins were found enriched with regards to their diet, due to the metabolic pathways of these animals.…”
Section: Discussionmentioning
confidence: 87%
“…different food digestibility, possible animal preference of one constituent in respect to another, delay between food ingestion and milk production, energy negative balances that may occur when energy spent for milk production exceed that acquired by food. 23 Focusing on the 13 C trend of milk and mozzarella over time, for the farm Ce1 ( Fig. 1(a)) it was possible to note an increasing trend from September 2016 to February 2017, even if the values were inside the standard deviation of the average.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Of the naturally occuring components, the difference in carbon stable isotope composition between the lipid (triacylglycerols/sterols) and lipid‐free (protein/carbohydrate) components (Δ 13 C lipid‐lipid free ) is particularly conspicuous, with lipids possessing lower δ 13 C values due to enzymatic fractionations during formation . Δ 13 C lipid‐lipid free values of −3.3 and −3.5‰ were determined for stall‐ and pasture‐fed cows, respectively, on long‐term, isotopically consistent diets . The similar offset between the Δ 13 C lipid‐lipid free value (−3.76‰) calculated in our study and the values from controlled feeding studies with homogeneous diets suggests that dairy cattle on conventional U.S. dairy farms are close to isotopic equilibrium, i.e., their diets are homogeneous over a long period of time, and that the effect of varying lipid concentrations on the isotopic composition of milk may be predictable.…”
Section: Discussionmentioning
confidence: 88%